Ease of Doing Business and Entrepreneurial Growth in the Face of Global Economic Policy Uncertainty - , Linus, Justin Ogbonna, Faith Chidimma Lawal, Sunday O. Okafor (Archives of Current Research International, 2024)
This study investigates the impact of ease of doing business on entrepreneurial growth in Nigeria from 2010 to 2023, particularly in the context of global economic policy uncertainty. Using data from the Global Entrepreneurship Monitor and the World Development Indicator, the study applies an Autoregressive Distributed Lag (ARDL) model to analyze the relationship between ease of doing business factors, such as access to credit, contract enforcement, and regulation, and entrepreneurial activity. The findings show that while improvements in the business environment significantly foster entrepreneurship, economic uncertainty hampers its growth. The study recommends that Nigeria should enhance its business environment and create safety nets to mitigate the adverse effects of global economic uncertainties. These insights are valuable for policymakers aiming to promote entrepreneurship and economic resilience in developing countries.